REGIONAL MEETING OF THE ARMENIAN REVOLUTIONARY PARTY IN CONSTANTINOPLE IN 1919 - Stepanyan, Khachatur (Armenian Folia Anglistika, 2025)
The article offers a historical analysis of the regional meeting of the Constantinople Branch of the Armenian Revolutionary Federation (ARF), held between June and August 1919. This gathering was particularly significant as it marked the first regional meeting in Constantinople since 1915. The agenda was wide-ranging and thorough. Key reports were presented by the ARF’s Responsible Authority, the Central Committee, and various organizational bodies, reviewing their activities over the preceding period. A major portion of the meeting focused on internal organizational matters, including revisions to the party’s Statute, structural reforms, and issues related to trade unions, cooperatives, and labor organizations. The discussions also addressed the party’s relationships with neighboring countries, other political parties, the Armenian Patriarchate, national institutions, and the Turkish state. Special emphasis was placed on future propaganda strategies, particularly the role of the Azatamart newspaper. The meeting concluded with preparations for the upcoming 9th ARF General Meeting and the election of a new Central Committee to guide future initiatives.